2020
DOI: 10.1186/s12866-020-01964-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the msaABCR operon in implant-associated chronic osteomyelitis in Staphylococcus aureus USA300 LAC

Abstract: Background The msaABCR operon regulates several staphylococcal phenotypes such as biofilm formation, capsule production, protease production, pigmentation, antibiotic resistance, and persister cells formation. The msaABCR operon is required for maintaining the cell wall integrity via affecting peptidoglycan cross-linking. The msaABCR operon also plays a role in oxidative stress defense mechanism, which is required to facilitate persistent and recurrent staphylococcal infections. Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…We have found a positive regulatory role for the msaABCR operon in biofilm development (Sahukhal et al, 2015), capsule production (Batte et al, 2018), antibiotic resistance (Bibek et al, 2019), antibiotic tolerance (Sahukhal et al, 2017), response to oxidative stress, and intracellular survival (Pandey et al, 2019). Moreover, in a recent study, we observed that an msaABCR operon mutant is attenuated in rat models of acute and chronic implant-associated osteomyelitis (Sahukhal et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…We have found a positive regulatory role for the msaABCR operon in biofilm development (Sahukhal et al, 2015), capsule production (Batte et al, 2018), antibiotic resistance (Bibek et al, 2019), antibiotic tolerance (Sahukhal et al, 2017), response to oxidative stress, and intracellular survival (Pandey et al, 2019). Moreover, in a recent study, we observed that an msaABCR operon mutant is attenuated in rat models of acute and chronic implant-associated osteomyelitis (Sahukhal et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Biofilms are well recognized as a source of recalcitrant bacteria that can impair antibiotic treatment of osteomyelitis and cause persistent or recurrent osteomyelitis, particularly when orthopedic implants are in place ( 13 , 31 , 111 ). Two studies that have pursued the in vivo investigation of biofilm virulence factors and genetic components in rats include the investigation by Wu et al ( 107 ), which demonstrated that overexpression of AS yycG led to a reduction in biofilm formation and in vivo pathogenicity of MRSA in a model of rat tibial osteomyelitis; as well as the investigation by Sahukhal et al ( 110 ) who utilized a model of implant-associated osteomyelitis. This investigation demonstrated that deletion of the msaABCR operon of S. aureus (USA300 LAC) resulted in defective biofilm production and reduced severity of bacterial osteomyelitis.…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…Staphylococcus aureus is the most common pathogens in endosseous implants infection. And the indiscriminate use of antibiotics has resulted in bacteria developing resistance to antibiotics [ 39 ]. And non-controllable drug-loaded antibacterial coatings cannot achieve the prevention of mid- and late-stage infections, and also can cause bacteria to develop resistance to antibiotics.…”
Section: Introductionmentioning
confidence: 99%